Direct on-target temporal measurement of high-intensity laser pulses during laser-matter interactions - Crespo,HM; Witting,T; Canhota,M; Miranda,M; Tisch,JWG (2020)
We present a new dispersion-scan-based technique for the temporal characterization of ultrashort laser pulses directly on target and at full laser power. We demonstrate the technique by measuring intense 4-fs pulses in conditions optimized for HHG.